HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN KETEPATAN SERVIS ATAS PADA SISWA PUTRA EKSTRAKULIKULER SMA NEGERI 1 PEKANBARU - Kevin Tri Ananda; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : The problem in this study is based on observations of ball blow when the ball service is often out of the field and sometimes stuck on the net or hit on the bet. This means that the top players performed by the players are not on target, or the service accuracy of them is still low. At the top serve is an initial attack that can generate points or points in winning in a game. ideally a strong and strong service will give your own level of difficulty to the recipient of service, even a service that is difficult to be accepted by the opposing team, if that happens then the addition of numbers for the team that serve the ball. The low service blow on the students is suspected because the upper serving blows lack the muscle power of the arms and shoulders causing the ball not to enter or exit from the field of volleyball. The purpose of this study was to determine the relationship of arm muscle and shoulder muscles with top service accuracy in students extracurricular son SMA Negeri 1 Pekanbaru. This type of research is correlational, Corelational is a statistical tool, which can be used to compare the measurement results of two different variables. The population in this study were students of extracurricular son of SMA Negeri 1 Pekanbaru who enrolled or actively followed the exercise that is as many as 17 people. The sampling technique, using total sampling technique. Based on the results of research can be drawn conclusions and suggestions that power arm and shoulder relations with the results of the up service volleyball in the sport bolavoli SMA Negeri 1 Pekanbaru. The result of analysis shows that rhitung 0,719> rtabel 0,497 at α = 0,05.Keywords : Relationships, Power Sleeve Muscles And Shoulder Upper Service Accordance